2015
DOI: 10.1039/c5ta04673d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical mesoporous/macroporous Co3O4 ultrathin nanosheets as free-standing catalysts for rechargeable lithium–oxygen batteries

Abstract: Hierarchical mesoporous/macroporous ultrathin Co3O4 nanosheets were synthesized as free-standing catalysts for Li–O2 batteries. Morphology of Li2O2 could be changed by controlling the shape of catalysts..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…It is also found that the obtained capacity of the CNTs/Co 3 O 4 p‐NRs is higher than that of the theoretical capacity of Co 3 O 4 (890 mA h g −1 ). Similar results have been reported in other transition‐metal oxides (TMOs) . The additional capacity might be due to enhanced lithium storage sites in the surface, pores, and interfaces of the nanoscale TMOs, according to the interfacial lithium storage mechanism …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It is also found that the obtained capacity of the CNTs/Co 3 O 4 p‐NRs is higher than that of the theoretical capacity of Co 3 O 4 (890 mA h g −1 ). Similar results have been reported in other transition‐metal oxides (TMOs) . The additional capacity might be due to enhanced lithium storage sites in the surface, pores, and interfaces of the nanoscale TMOs, according to the interfacial lithium storage mechanism …”
Section: Resultssupporting
confidence: 82%
“…Similarr esults have been reported in other transition-metal oxides( TMOs). [5,14,24] The additional capacitym ight be due to enhanced lithium storages ites in the surface, pores, and interfaces of the nanoscale TMOs, according to the interfacial lithium storagemechanism. [19,25] The rate performanceo ft he CNTs/Co 3 O 4 p-NR and Co 3 O 4 p-NR electrodes was also evaluatedb yc harging-discharging at differentc urrent densities, rangingf rom 0.5 to 8Ag À1 .T he CNTs/Co 3 O 4 p-NR electrode (Figure 8b)s hows high reversible capacities of around 953, 906, 843, 718, and 677 mA hg À1 at currentd ensitieso f0 .5, 1, 2, 4, and 5Ag À1 ,r espectively.R emarkably,t he Co 3 O 4 -CNTse lectrode can still exhibit ac apacity of 521 mA hg À1 at ar elatively high current density of 8Ag À1 .I n addition, the capacity can be recovered to its initial value if the currentd ensity is reduced back to 0.5 Ag À1 ,w hich can be attributed to reactivation reactions resulting from the high rate of lithiation.…”
Section: Resultsmentioning
confidence: 99%
“…[192] The mesoporous/macroporous Co 3 O 4 nanosheets were obtained by calcining a Co(OH) 2 CO 3 precursor grown on a nickel foam substrate, and had a thickness of around 5 nm, a specific surface area of 62.72 m 2 g −1 , and a typical mesoporous structure with a main pore size of about 3 nm. [192] The mesoporous/macroporous Co 3 O 4 nanosheets were obtained by calcining a Co(OH) 2 CO 3 precursor grown on a nickel foam substrate, and had a thickness of around 5 nm, a specific surface area of 62.72 m 2 g −1 , and a typical mesoporous structure with a main pore size of about 3 nm.…”
Section: Cobalt Oxide Nanosheetsmentioning
confidence: 99%
“…The thin lm formed aer 1 st discharge sticks closely to the nanosheets and becomes thicker when discharging to higher capacities. 7,[40][41][42] Subsequently, all discharging products were almost fully decomposed from the surface of both GDL-Co 3 O 4 NSs and GDL-Co 3 O 4 NSs-30Au electrodes aer recharging (Fig. S10b-f †).…”
Section: Resultsmentioning
confidence: 98%